Development of approaches and organizational models for the mass implementation of information modeling technologies in the investment and construction sphere - Anatoly Platonov; Viola Larionova; Yury Davy (Journal of Risk and Financial Management, 2023)
The rapidly increasing use of building information modeling (BIM) technologies in the world is highly relevant to the search for new approaches and managerial models for enterprises in the construction sphere. As shown in the study of several developing countries, there is a certain lag in this area compared with highly industrialized countries. A comparative analysis of countries in terms of the level of spread of BIM technologies was made using open data from job search Internet sites. In this regard, the urgency of the research is due to the need to develop appropriate approaches to intensify the implementation of BIM technologies in the construction and operation of buildings. The purpose of the study is the development of methodological foundations and applied models of functional interaction between participants of construction projects based on BIM. As a working hypothesis, the authors assume that the mass application of BIM technologies is possible in providing a set of measures of different nature: market, non-market, legal, economic, and organizational. The main results of the study provided a solution to the problem of a significant expansion of the scope of BIM technologies in the construction sector through the formation of an information eco-environment for interaction of participants in the project management system.
Keywords: 650; BIM technologies; building information modeling; construction; development; innovative process; investments; risks; software